OCCURRENCE OF POTENTIALLY HAZARDOUS FUNGI IN EXPOSED BREWERY SPENT SORGHUM GRAINS - Onyimba, Isaac A.; Ogbonna, Chike I. C.; O. O. Chukwu, Chukwu; Odu, Collins C. E. (European Scientific Journal, ESJ, 2014)
Samples of environmentally exposed spent sorghum grains (SSG), commonly used as feedstuff in Nigeria, were obtained from the Jos International Brewery and screened for potentially harzardous fungi associated with them. A total of three samples, one per week, were used in the study. Truly colonizing fungi of the SSG were further determined by assessing the abilities of the fungal isolates to grow on specially formulated spent sorghum grain agar (SSGA). Fourteen fungal species belonging to nine genera were isolated from the SSG. Frequently occurring fungi included Aspergillus niger (89%), A. fumigatus (56%), A. flavus (78%), Rhizopus, oryzae (78%) and R. stolonifer (56%). The genus Aspergillus had the highest number of species (28.6%) among the isolates. The true fungal colonizers of SSG were found to include A. flavus, A. fumigatus, A. niger, A. ochraceus, Curvularia lunata, Geotrichum candidum, Humicola grisea, Penicillium sp, R. oryzae, R. stolonifer and Trichoderma harzianum. Among the fungal isolates were species that have been known to contain either pathogenic or toxigenic strains. The findings from the experiments showed that exposed SSG can be colonized by potentially hazardous fungi and as such, caution should be exercised in its use as a feedstuff.